MODERN DIAGNOSTIC AND THERAPEUTIC APPROACHES IN LIVER CIRRHOSIS: THE ROLE OF INNOVATIVE TECHNOLOGIES AND BIOMARKERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Liver cirrhosis remains one of the most challenging chronic liver diseases in modern hepatology, characterized by progressive hepatic dysfunction and the development of multiple systemic complications, including renal impairment. This article highlights the significance of advanced medical technologies and innovative diagnostic and therapeutic strategies in the comprehensive management of patients with liver cirrhosis. The integration of targeted pharmacotherapy, regenerative medicine concepts, and novel biomarkers has substantially improved early diagnosis, risk stratification, and treatment outcomes in cirrhotic patients. The study emphasizes the role of modern diagnostic tools and personalized therapeutic approaches in improving clinical outcomes, quality of life, and overall survival of individuals with liver cirrhosis. The implementation of cutting-edge technologies represents a promising direction for optimizing patient-centered care in hepatology.